ENTREPRENEURIAL ORIENTATION (EO) AND PERFORMANCE OF FAMILY BUSINESS (FB): AN EMPIRICAL ANALYSIS (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2024)
The study explores entrepreneurial orientation and performance of family businesses. The impetus for this research arises from the common failures experienced by family businesses, often due to inadequate business orientations that impede success. Factors contributing to these failures include limited financial resources, poor infrastructure, unfavorable government policies, insufficient sales, and excessive taxation. The study utilized content analysis to review existing studies on the subject. The research reveals a positive relationship between proactiveness, innovativeness, and risk-taking with family business performance in Nigeria. The study concludes that businesses with an entrepreneurial orientation often lead their industries through innovative practices, improving customer satisfaction and gaining a competitive edge. The study recommends that family business owners and managers prioritize continuous improvement and radical innovation to expand their customer base and enhance overall performance.